Answer: -4/15
Step-by-step explanation: To add these two fractions together,
we start by finding their <em>Least Common Denominator</em> (LCD).
Since our denominators of 5 and 3 have no factors in common,
our least common denominator is 5 · 3 or 15.
In order to get a denominator of 15 in each fraction,
we multiply top and bottom of the first fraction by 3
and top and bottom of the second fraction by 5.
That gives us -9/15 + 5/15 which simplifies to -4/15.
As your last step, make sure that the fraction
that you end up with doesn't reduce.
In this case, -4/15 does not reduce but watch out for this last step.
Answer:
x = 5
y = 4
Step-by-step explanation:
multiply the second equation by -1 and add the first equation to eliminate "x"
![4x+6y=44\\-4x-2y=-28](https://tex.z-dn.net/?f=4x%2B6y%3D44%5C%5C-4x-2y%3D-28)
_____________
![4y=16](https://tex.z-dn.net/?f=4y%3D16)
![y=16/4 =4](https://tex.z-dn.net/?f=y%3D16%2F4%20%3D4)
Replace "y" in the first equation:
![4x+6(4)=44](https://tex.z-dn.net/?f=4x%2B6%284%29%3D44)
![4x+24=44](https://tex.z-dn.net/?f=4x%2B24%3D44)
![4x=44-24](https://tex.z-dn.net/?f=4x%3D44-24)
![x=20/4=5](https://tex.z-dn.net/?f=x%3D20%2F4%3D5)
Hope this helps
Answer:
The remainder is 5
Step-by-step explanation:
12 Divided by 7 equals 12 over 7 or 1.714285. 7 can only go into 12, one time. if we subtract 7 from 12 we get 5 which is the remainder. There is no way it can be 2 because 7 plus 2 equals 9. 1 x 7 + 5 equals 12 which isn't 1.714285. 2 x 7 + 4 equals 18 which also isn't 1.714285. Same with 2 x 5 + 5. That equals 15 which isn't 1.714285.
For this case we have that by definition, the standard form of the equation of the line is given by:
![ax + by = c](https://tex.z-dn.net/?f=ax%20%2B%20by%20%3D%20c)
We have the following equation:
![y-2 = - \frac {3} {2} (x + 6)](https://tex.z-dn.net/?f=y-2%20%3D%20-%20%5Cfrac%20%7B3%7D%20%7B2%7D%20%28x%20%2B%206%29)
We manipulate the equation algebraically:
![y-2 = - \frac {3} {2} x- \frac {3 * 6} {2}\\y-2 = - \frac {3} {2} x \frac {18} {2}\\y-2 = - \frac {3} {2} x-9\\y-2 + 9 = - \frac {3} {2} x\\y-7 = - \frac {3} {2} x\\2 (y-7) = - 3x\\2y-14 = -3x\\3x + 2y = 14](https://tex.z-dn.net/?f=y-2%20%3D%20-%20%5Cfrac%20%7B3%7D%20%7B2%7D%20x-%20%5Cfrac%20%7B3%20%2A%206%7D%20%7B2%7D%5C%5Cy-2%20%3D%20-%20%5Cfrac%20%7B3%7D%20%7B2%7D%20x%20%5Cfrac%20%7B18%7D%20%7B2%7D%5C%5Cy-2%20%3D%20-%20%5Cfrac%20%7B3%7D%20%7B2%7D%20x-9%5C%5Cy-2%20%2B%209%20%3D%20-%20%5Cfrac%20%7B3%7D%20%7B2%7D%20x%5C%5Cy-7%20%3D%20-%20%5Cfrac%20%7B3%7D%20%7B2%7D%20x%5C%5C2%20%28y-7%29%20%3D%20-%203x%5C%5C2y-14%20%3D%20-3x%5C%5C3x%20%2B%202y%20%3D%2014)
Finally, the equation is:
![3x + 2y = 14](https://tex.z-dn.net/?f=3x%20%2B%202y%20%3D%2014)
Answer:
![3x + 2y = 14](https://tex.z-dn.net/?f=3x%20%2B%202y%20%3D%2014)